A simply enzymatic hydrolysis pretreatment for β-mannanase production from konjac powder. (February 2018) - You, Shengping; Ding, Juanjuan; Dai, Yemei; Xing, Ruizhe; Qi, Wei; Wang, Mengfan; Su, Rongxin; He, Zhimin
Graphical abstract: Highlights: A new fermentation based on enzymatic hydrolysis of konjac powder was developed. Operational difficulties in the traditional fermentation were solved. The new process was simple and efficient for industrial-scale. It can be used to utilize other mannan-based bioresource for β-mannanase production. Abstract: Currently, the traditional fermentation using konjac powder for β-mannanase production presents operational difficulties and high energy consumption, because of the individual hot air sterilization for konjac powder. A simply enzymatic hydrolysis pretreatment for konjac powder was developed to solve the problems of the traditional process in a 7-L fermenter. In the new process, when hydrolysis yield of konjac powder was above 50%, the media became liquid state from gelatinous state and could be sterilized immediately, avoiding the hot air sterilization and solving the operational difficulties. Interestingly, the new process didn't have negative influence on β-mannanase production. Additionally, it could save close to 23% of power consumption during the whole fermentation. For another example, it did work well using locust bean gum for β-mannanase production in a 7-L fermenter. Therefore, the new process might be scaled up for industrial production using mannan-based bioresource as substrate.